PENERAPAN ALGORITMA BLOB DETECTION DAN OPERATOR SOBEL PADA APLIKASI PENGENALAN OBJEK CITRA PLAT NOMOR KENDARAAN - Riyadi Iskandar; Kartono Kartono; Agusalim Agusalim (INTEKSIS, 2021)
Object recognition is a technique for the identification of a specific object from an image by using a specific algorithm. This object recognition techniques can be applied to many things, one of which is to recognize the image of the vehicle license plates. Vehicle license plate is an identity for each vehicle. Some of the Supporting methods that can be used to perform object recognition i.e. Sobel operator and Blob detection. The algorithm will analyze images captured by a camera that can recognize objects such as license plate numbers and then the feature in the image blob detection results will be classified so it can be identified. Through this study, the authors wanted to design an application that apply image processing techniques using Sobel operator and blob detection algorithm to detect objects contained in a license plate. Keywords : Object Recognition,Vehicle License Plate,  Software, Algorithm,Sobel Operator, Blob Detection